VISUAL ORGANIZERS AS SCAFFOLDING TECHNIQUES IN TEACHING ENGLISH IN NONPHILOLOGICAL UNIVERSITIES - Azizova Gulnora Shakirdjanovna Senior Teacher of the National Institute of Fine Arts; Design named after Kamoliddin Bekhzod (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article is devoted to the methods of teaching a foreign language in non-philological higher education institutions and the problems of language learning. In addition, the article describes the effectiveness of using visual aids. Keywords: Visualization, language, method, skill, technology.